2019
DOI: 10.1039/c9ra08096a
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics profiling of methamphetamine addicted human serum and three rat brain areas

Abstract: Methamphetamine (METH) has already been a serious problem all over the world. The identification of related biomarkers and pathways is helpful to evaluate the degree of METH addiction, develop appropriate treatment during abstinence, and explore the mechanism. Here, it is the first time to perform metabolomics profiling of METH addicted human serum and three regions of METH-induced conditioned place preference (CPP) rat brain by using UHPLC-MS/MS and matrix-assisted laser desorption/ionization-mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 50 publications
5
15
2
Order By: Relevance
“…Together with a general increase in nucleotides like ADP, GMP and AMP in nucleus accumbens and dorsal hippocampus (but a decrease in the ventral hippocampus), these findings point towards an alteration in energy homeostasis in a brain region-dependent manner. A reduction in the antioxidant GSH was reported in both studies (Bu et al, 2013;Lin et al, 2019). Moreover, a reduction in N-acetylaspartate and an increase of phosphocholine were observed in brain regions of chronically treated rats, indicating that oxidative damage was present alongside neuronal and mitochondrial dysfunction (Bu et al, 2013).…”
Section: Metabolic Signature Of Methamphetamine Addictionmentioning
confidence: 81%
See 3 more Smart Citations
“…Together with a general increase in nucleotides like ADP, GMP and AMP in nucleus accumbens and dorsal hippocampus (but a decrease in the ventral hippocampus), these findings point towards an alteration in energy homeostasis in a brain region-dependent manner. A reduction in the antioxidant GSH was reported in both studies (Bu et al, 2013;Lin et al, 2019). Moreover, a reduction in N-acetylaspartate and an increase of phosphocholine were observed in brain regions of chronically treated rats, indicating that oxidative damage was present alongside neuronal and mitochondrial dysfunction (Bu et al, 2013).…”
Section: Metabolic Signature Of Methamphetamine Addictionmentioning
confidence: 81%
“…Succinic acid semialdehyde levels increased, consistent with its role as an intermediate of GABA catabolism. A decrease in Glu and Gln was also observed in the nucleus accumbens and dorsal hippocampus by Lin et al (2019), although these metabolites, along with the amino acid and excitatory neurotransmitter aspartate, were down-regulated in the ventral hippocampus. Together, these findings suggest that the disturbance to Gln-Glu-GABA axis in the brain may be involved in the behavioural sensitisation to methamphetamine.…”
Section: Metabolic Signature Of Methamphetamine Addictionmentioning
confidence: 90%
See 2 more Smart Citations
“…Based on the theory proposed from the development of methadone maintenance programs, addiction could be considered a metabolic disease as it initiates from a disruption in metabolism and causes persistent neurochemical disturbances leading to addiction [ 8 , 9 ]. Several metabolomic studies in animals were recently conducted to investigate MA use and revealed that MA exposure caused an imbalance in metabolites related to energy metabolism, amino acid metabolism, phospholipids metabolism, oxidative stress, and neurotransmitters [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ] However, the altered metabolites or metabolic pathways were inconsistent, depending on the doses and durations of MA administration and targeted animal model samples [ 17 ]. Moreover, knowledge gained from the metabolic analysis is often fragmentary owing to the bottleneck in identifying metabolites in case of untargeted metabolomics and the lack of further in-depth study based on the biological importance of metabolic alterations caused by MA.…”
Section: Introductionmentioning
confidence: 99%